P356Effect of catheter ablation on left and right ventricular function in patients with frequent premature ventricular contractions and preserved ejection fraction. (18th June 2020) - Stassen, J; Dilling, D; Vijgen, J; Scherrenberg, M; Schurmans, J; Verwerft, J; Koopman, P
Abstract: INTRODUCTION: Improvement of left ventricular ejection fraction (LVEF) after catheter ablation (CA) in patients with left ventricular (LV) dysfunction and frequent premature ventricular contractions (PVCs) of the outflow tract (OT) has been reported. However, many patients with PVCs of the OT have a normal LVEF. The effect of CA on the left and right ventricular function in these patients is not well established.   PURPOSE   This study aims to evaluate the effect of CA on improvement of left and right ventricular function in patients with a preserved LVEF (EF > 50%) and frequent PVCs originating from the OT.  METHODS   We retrospectively examined clinical, electrophysiological and echocardiographic measurements in 95 patients with a preserved LVEF and frequent PVCs from the OT who underwent CA, dating from January 2014 till December 2018. Two dimensional TTE was performed at baseline and follow up. LV volumes and LVEF were calculated using the Simpson's method. LV global longitudinal strain (GLS) and RV free wall longitudinal strain were calculated by 2D speckle tracking.  The Shapiro-Wilk test was used to determine the normal distribution of all variables. The Wilcoxon Signed Rank test was used to compare the evolution of the categorical and continuous variables between the TTE at baseline and follow-up.  RESULTS   Mean age of our study population was 52.8 ± 16.6 years, 49% was female. Mean burden of PVC before ablation was 18423 (2496-54000)/24h; 23.2% had a burden of less than 10.000 PVCs/24h. Mean burden of PVC after ablation was 1403 (0-27349)/24h. Median time between ablation and follow-up TTE was 117, 8 days. There was a significant amelioration of LVEF (54.0 ± 4.0 vs 58.0 ± 3.8%, p <0.001) and LV GLS (18.4 ± 2.2 vs 20.4 ± 2.0 %, p < 0.001) as well as TAPSE (24.8 ± 3.5 vs 25.2 ± 3.1mm, p 0.013) and RV strain (25.4 ± 3.9 vs 27.6 ± 3.7%, p <0.001). There was no significant difference in LV end diastolic diameter (50.1 ± 5.6 vs 49.6 ± 5.3mm, p 0.06) or LV end diastolic volume (109.7 ± 27.8 vs 107.2 ± 24.9mm, p 0.25), but there was a significant reduction in LV end systolic volume  (50.7 ± 13.9 vs 44.7 ± 11.1mm, p < 0.001). RV basal diameter was not different (33.8 ± 4.5mm vs 33.6 ± 4.2mm, p 0.30).In the patient group with VES <10000/24h, there was no significant difference in LVEF (55, 2 ± 4, 6 vs 55, 9 ± 4, 6%, p 0, 12), but there was a significant amelioration of GLS (18.4 ± 2.2 vs 19.9 ± 2.1%, p < 0.001) and RV strain (24.1 ± 4.3 vs 25.9 ±3.3%, p0.003). In the patient group with VES >10000/24h, beneficial effects were noticed in LVEF (53.6 ± 3.8 vs 58.7 ±3.2%, p < 0.001), GLS (18.4 ± 2.2 vs 20.5 ± 2.0%, p < 0.001) and RV strain (25.8 ± 3.7 vs 28.1 ± 3.7%, p < 0.001). CONCLUSION: Frequent PVCs from the OT can induce subtle cardiac dysfunction in patients without apparent cardiomyopathy. CA can improve left and right ventricular function in these patients, which can be detected by conventional TTE parameters but also in an earlier stage by 2D speckle tracking.